Kano-QFD-based analysis of the influence of user experience on the design of handicraft intangible cultural heritage apps - Jia Li; KieSu Kim (Heritage Science, 2023)
Abstract Mobile internet and digital technology provide new media platforms for the dissemination of handicraft intangible cultural heritage (ICH). Despite extensive research into the effect of user experience (UX) on handicraft ICH applications (apps), there is little quantitative research on the relationship between user needs and app design requirements. This study employed semi-structured interviews, online questionnaire surveys, and expert evaluation to understand and rank user needs and design requirement influencing factors. A quantitative analysis using the Kano-QFD approach revealed the different effects of twelve user needs and twenty-three design requirements on handicraft ICH app design. Following the establishment of a relationship matrix between user needs and design requirements, the app design requirements were ranked according to importance. Furthermore, a concept–category–application UX app design framework was constructed based on an analysis of the importance of design requirements. The concept layer formed the theoretical basis for the UX app design, the category layer represented the different facets of the UX design, and the application layer provided specific suggestions on the importance of app design. The eye-movement experiment and System Usability Scale were used to test the UX effects of a sample handicraft ICH app, verifying that the UX design framework was reliable. The framework provides methodological reference for the UX design of other ICH digital products.